2020
DOI: 10.3390/app10196799
|View full text |Cite
|
Sign up to set email alerts
|

Arching Detection Method of Slab Track in High-Speed Railway Based on Track Geometry Data

Abstract: During the long-term service of slab track, various external factors (such as complicated temperature) can result in a series of slab damages. Among them, slab arching changes the structural mechanical properties, deteriorates the track geometry conditions, and even threatens the operation of trains. Therefore, it is necessary to detect slab arching accurately to achieve effective maintenance. However, the current damage detection methods cannot satisfy high accuracy and low cost simultaneously, making it diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To solve the arching problem for granular materials, in terms of taking the arching phenomenon as the research object, Jenike used the flow factor to study the arching of granular material particles in the hopper in the early stage and found that the flow factor is related to the friction angle of material particles and the friction angle in the hopper [8]. In recent years, there have been an extensive number of studies on soil-particle-arch formation [9,10] and track-slab-arch detection [11]. Nikiitenko proposed measures of staticarch stabilization that affected the quality of drainage construction by mathematically simulating the arching of loose materials in the drainage hangar [12].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the arching problem for granular materials, in terms of taking the arching phenomenon as the research object, Jenike used the flow factor to study the arching of granular material particles in the hopper in the early stage and found that the flow factor is related to the friction angle of material particles and the friction angle in the hopper [8]. In recent years, there have been an extensive number of studies on soil-particle-arch formation [9,10] and track-slab-arch detection [11]. Nikiitenko proposed measures of staticarch stabilization that affected the quality of drainage construction by mathematically simulating the arching of loose materials in the drainage hangar [12].…”
Section: Introductionmentioning
confidence: 99%
“…A ballastless track slab is an important part of various types of track structures, as it plays a "top-down" role (i.e., bearing the train load and transferring it down to the foundation) [3]. However, prolonged operation could cause various defects in track slabs, such as warping deformation of track slab [4,5], wide and narrow joint damages [6,7], interlayer debonding [3,8,9], and arching deformation of track slab [10][11][12]. Under temperature load [13,14] and high-frequency train load [14], these damages may cause track slab deformation and abnormal vibrations in wheel-rail system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the real-time monitoring of track slab performance and the identification of the damage condition of track slabs are essential for long-term safe operation of the HSR. Existing track slab defect detection methods can be divided into three categories: visual inspection [15,16], nondestructive testing (NDT) [4,11,[17][18][19][20][21][22], and structural health monitoring (SHM) [23][24][25][26][27]. Most of the visual inspection methods rely on a variety of track inspection equipment, such as road rulers, gauges, and various customized equipment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations